Restriction Policy on Afghan Girls' Education and its Consequences - Hamidi, Abdul Basir (Edukasiana: Jurnal Inovasi Pendidikan, 2024)
The people of Afghanistan experienced profound transformations across various spheres following the political upheaval of August 15, 2021, wherein the Islamic Republic government was replaced by the Islamic Emirate of Afghanistan. The new government has introduced various policies that are impacting people's lives differently from before. One of these policies is placing  limitations on the education of women, signaling a significant shift in how educational opportunities are being provided to female students. The study adopted a qualitative case study with a sample of female school students across five provinces of Afghanistan, including Kabul, Herat, Bamiyan, Farah and Jalalabad. Each of the five provinces represented by 10 students, for 50 respondents. The findings of the research highlights that depriving girls of education has had a number of detrimental effects on them, including emotional and psychological issues, forced marriage, migration, a loss of hope for the future, and other long-term effects. The study highlights the value of providing girls with equal educational opportunities and contributes to the creation of more effective policies and methods to guarantee girls' access to education in Afghanistan and other countries facing similar difficulties.